Patient Perceptions and fetal outcome of Cesarean delivery on Maternal request at Birat Medical College Teaching Hospital - Pradhan, Tarun; Mahato, Raj Deb; Dhamala, Jiba Nath; Dahal, Prerana (Nepal Journal of Obstetrics and Gynaecology, 2022)
Aims: To explore the patient profile and perceptions of patient for choosing cesarean delivery on request over vaginal delivery. Methods: The study is a prospective cross-sectional observational study from Jan 2021 to Dec 2021 in the Department of Obstetrics and gynecology, BMCTH. The data were entered in an excel sheet. Statistical analysis was done for frequency and percentage for categorical variables. Results: Out of 1413 cesarean sections 106 underwent on their request without obstetrical indications. requested for cesarean delivery by maternal request. Prevalence of CDMR of total number of delivery in our institute was found to be 3.3. Fear of labor pain (53.8%) was the most common reason for CDMR followed by 39.6% of the lady choose because of concern of fetal injury during labor. Despite CDMR, 10 fetus required NICU admission. Conclusions: The perception of pregnant women for choosing CDMR showed to be influenced by multiple factors; the most important is to avoid pain during labour and fera of fetal injury during vaginal delivery. Keywords: cesarean delivery; maternal request; neonatal outcome